UNB'S Distance Education Center in the context of internationalization: integration of innovative educational actions with the use of digital technologies - Ferreira, Marcello (2020)
This study deals with the actions of the Distance Education Center (CEAD) of the University of Brasília (UnB) in the scenario of educational internationalization. It considers internationalization as a process of integrating an international and intercultural dimension in higher education, through interaction and collaborative practices. In order to analyze CEAD's actions aimed at internationalization, with a focus on extension, exploratory research, after documentary analysis, revealed that this Center contributes to innovative actions, through the Open University of Brazil and Learning for the 3rd Millennium programs (A3M), with emphasis on the agreement with the Open University of Portugal (UAb) and materializes, primarily, in dissemination actions.